2014
DOI: 10.4103/2277-9175.125764
|View full text |Cite
|
Sign up to set email alerts
|

Risks of concomitant trauma to the knee in lower limb long bone shaft fractures: A retrospective analysis from a prospective study population

Abstract: Background:Numerous associated injuries (bony and/or soft tissue lesions) occur commonly in conjunction with fractures of the femoral shaft in young patients after high-energy injuries. Knee ligamentous injuries, historically called as the internal derangements of the knee or IDK, are mostly not visible in plain radiographs taken in the emergency and these injuries are likely to be overlooked by clinicians because first attention always goes to open wounds and radiologically visible injuries of the limb whenev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…[ 3 ] Kumar found that ligament injury was commonly companied by either a medial or lateral meniscus injury. [ 18 ] Given such hidden complications, meticulous examination of the knee and recognition of ligament and meniscus injuries are really essential. [ 3 ] Surgical stabilization of both fractures, respectively, is the recommended treatment for floating knee injury currently.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Kumar found that ligament injury was commonly companied by either a medial or lateral meniscus injury. [ 18 ] Given such hidden complications, meticulous examination of the knee and recognition of ligament and meniscus injuries are really essential. [ 3 ] Surgical stabilization of both fractures, respectively, is the recommended treatment for floating knee injury currently.…”
Section: Discussionmentioning
confidence: 99%